2017
DOI: 10.1097/md.0000000000006949
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cystatin C and glomerular filtration rate in diagnosis of kidney impairment in hepatic cirrhosis patients

Abstract: Hepatic cirrhosis is often accompanied by functional kidney impairment, which may be reversed if early treatment is promptly administered. This study aimed to investigate the role of Cystatin C and Cystatin C estimated glomerular filtration rate in the diagnosis of kidney impairment in patients with hepatic cirrhosis.Four hundred sixty five patients with hepatic cirrhosis were recruited. Serum creatinine and Cystatin C were determined, and their estimated glomerular filtration rates were calculated.The area un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Interstignly, Cystatin-C values were moderately but signi caly higher in the Child C group 24 hours after OLT. This increase is consistent with recent studies showing that Cystatin-C is a more sensitive indicator for renal impairment in cirrothic patients than serum creatinine and creatinine clearance [40]. Moreover, higher values of Cystatin-C were correlated with a more severe cirrothic disease [41] and has been shown to be an independent predictor of post OLT survival [42].…”
Section: Renal and Neurohormonal Responses During Surgery And 24 H Afsupporting
confidence: 91%
“…Interstignly, Cystatin-C values were moderately but signi caly higher in the Child C group 24 hours after OLT. This increase is consistent with recent studies showing that Cystatin-C is a more sensitive indicator for renal impairment in cirrothic patients than serum creatinine and creatinine clearance [40]. Moreover, higher values of Cystatin-C were correlated with a more severe cirrothic disease [41] and has been shown to be an independent predictor of post OLT survival [42].…”
Section: Renal and Neurohormonal Responses During Surgery And 24 H Afsupporting
confidence: 91%
“…Conversely, serum cystatin C (CysC)-based estimated GFR (CysCGFR) shows improved correlation with measured GFR and improved predictability for overall survival and incidence of acute kidney injury compared with CrGFR (2-4). CysC appears to be more sensitive than Cr for patients with declining GFR in chronic liver disease (3)(4)(5). However, CysC positively correlates with body mass index (BMI) and is more strongly correlated with waist circumference and inflammation (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Although the two indicators eGFR CysC and eGFR Creat were both applied in the Chinese group, our findings showed that eGFR CysC had a higher performance in the diagnosis of kidney impairment in LNA. Moreover, the evidence is available that the measurement of Creat to determine the eGFR is limited by the influence of age and sex, as well as the variability in the clinical methodology for Creat determination [34, 35]. As known, the enzyme method is widely used in the majority of laboratories.…”
Section: Discussionmentioning
confidence: 99%